University of Colorado 1975 Field Season on Baffin Island - Andrews, John T. (ARCTIC, 1976)
Eight individual research programmes were carried out by graduate students and one faculty member of the University's Institute of Arctic and Alpine Research (INSTAAR) during the 1975 field season. They were concentrated around the settlements of Broughton Island and Pangnirtung as well as the DEW line station at Cape Dyer. Field operations were facilitated by an early break-up, which permitted sea travel by canoe. . Two investigations were carried out from . [Pangnirtung]. The first concerned the Holocene climate of the area. . The other study involved the surveying of ten moraine systems fronting individual cirque glaciers. The volume of the ice core and surficial and englacial till was measured. The figures obtained will be used in a study of contemporaneous rates of glacial erosion in these subpolar glaciers. The first of two research projects based around Cape Dyer was a study of the Quaternary geology of the area between Sunneshine and Monneshine Fiords. . The second programme involved a study of the elevational limits of various types of "lichen-free" areas, varying from trimlines around glaciers to extensive areas on plateaus that were once mantled by a permanent or semi-permanent snow cover. Dating of the onset and disappearance of snow cover was carried out by lichenometry, and samples of dead vegetation (Salix) were collected for radiocarbon dating. Field programmes in Quaternary geology, plant ecology and palynology, limnology and fast-ice studies were carried out. . Studies of water temperature and other standard measurements were carried out at several lakes. Planktonic hauls were made, and a study performed, on the effect of light on plankton levels. Field measurements on surface energy budget components were completed. They were designed to assist in improvising INSTAAR's fast ice melt-stage model. The local measurements at Broughton Island were supplemented by several flights in the Canadian Ice Reconnaissance Patrol over Davis Strait.